Endothelial cells control vascular smooth muscle cell cholesterol levels by regulating 24-dehydrocholesterol reductase expression - Kohlhaas, Johanna; Jäger, Marius Andreas; Lust, Leandra; Torre, Carolina de la; Hecker, Markus; Korff, Thomas (Experimental cell research, 2021)
Communication of vascular cells is essential for the control of organotypic functions of blood vessels. In this context, vascular endothelial cells (EC) act as potent regulators of vascular smooth muscle cell (VSMC) functions such as contraction and relaxation. However, the impact of ECs on the gene expression pattern of VSMCs is largely unknown. Here, we investigated changes of the VSMC transcriptome by utilizing 3D human vascular organoids organized as a core of VSMCs enclosed by a monolayer of ECs. Microarray-based analyses indicated that interaction with ECs for 48 h down-regulates expression of genes in VSMCs controlling rate-limiting steps of the cholesterol biosynthesis such as HMGCR, HMGCS1, DHCR24 and DHCR7. Protein analyses revealed a decrease in the abundance of DHCR24 (24-dehydrocholesterol reductase) and lower cholesterol levels in VSMCs co-cultured with ECs. On the functional level, the blockade of the DHCR24 activity impaired adhesion, migration and proliferation of VSMCs. Collectively, these findings indicate that ECs have the capacity to instruct VSMCs to shut down the expression of DHCR24 thereby limiting their cholesterol biosynthesis, which may support their functional steady state.
Gesehen am 25.03.2021